A study of advanced visualization literacy - Firat, Elif Emel (2022)
Visualization literacy is essential with the widespread advent of visualization techniques to convey complex data. Two noteworthy facets of literacy are user understanding and the discovery of visual patterns with the help of graphical representations. This thesis focuses on studying and advancing visualization literacy and aims to assist understanding and interpretation of visual designs by developing interactive visualization techniques. Our primary objective is to study treemap and parallel coordinates graphic designs which are commonly used to display data. However, they are not easily understood visual representations.